1986
DOI: 10.1128/iai.52.3.846-852.1986
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary microvascular injury induced by Pseudomonas aeruginosa cytotoxin in isolated rabbit lungs

Abstract: The effects of Pseudomonas aeruginosa cytotoxin on the pulmonary microvasculature were studied in blood-free, perfused, isolated rabbit lungs. Cytotoxin was administered to the recirculating Krebs Henseleit albumin (1%) buffer during two consecutive 30-min-perfusion phases (phases 1 and 2) at a concentration of 13 ,ug/ml, followed by a third perfusion phase (phase 3) without toxin. After perfusion phases 2 and 3, the capillary filtration coefficient (Kf,c) and vascular compliance were determined gravimetrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 48 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…In our experimental model, the natural evolution of P. aeruginosa-induced pneumonia results in pulmonary epithelial and endothelial barrier disruption, interstitial and alveolar edema, and progression to acute lung injury (15,(21)(22)(23). Thus, we next examined the effects of caspase-1 inhibition on lung epithelial and endothelial barrier integrity, and lung function in response to P. aeruginosa infection.…”
Section: Resultsmentioning
confidence: 99%
“…In our experimental model, the natural evolution of P. aeruginosa-induced pneumonia results in pulmonary epithelial and endothelial barrier disruption, interstitial and alveolar edema, and progression to acute lung injury (15,(21)(22)(23). Thus, we next examined the effects of caspase-1 inhibition on lung epithelial and endothelial barrier integrity, and lung function in response to P. aeruginosa infection.…”
Section: Resultsmentioning
confidence: 99%
“…Induction of significant reactions in the rat lung model required approxi-mately 100 ng of purified SpeF in 1 ml of perfusion solution, a dose somewhat higher than those used for the induction of in vitro mitogenic activity by SpeF (16). Seeger and coworkers reported that several bacterial toxins including Escherichia coli hemolysin, Pseudomonas aeruginosa cytotoxin, and Staphylococcus aureus ␣-toxin induce lung vascular permeabilization in an isolated perfused rabbit lung model, very similar to the rat model used in this study; they showed that these toxins play important roles in the pathogenesis of ARDS caused by bacterial infections (1,21,24). SpeF may be a crucial factor for onset of ARDS during severe infection or TSLS caused by S. pyogenes.…”
Section: Discussionmentioning
confidence: 53%
“…There are a few possible mechanisms which would explain rat lung vascular permeabilization by SpeF. One is that mentioned by Seeger et al (1,21,24): SpeF would form pores on lung vascular endothelial cells and then causes sequential events which trigger arachidonic acid cascades and consequently causes lung vascular permeabilization. However, this is unlikely, because so far there is no evidence that SpeF has pore-forming ability.…”
Section: Discussionmentioning
confidence: 99%
“…It was first described by Scharmann (39) and originally called leukocidin because it had cytotoxic effects on leukocytes (40). It has since been shown to cause cytopathic effects in most types of eukaryotic cells by interacting with cell membranes (3,6,15,16,41,45). A survey of P. aeruginosa clinical isolates showed that all isolates produce cytotoxin (5), and its importance in pathogenesis is suggested by its cytotoxicity and the observation that patients with chronic P. aeruginosa infections have elevated levels of anticytotoxin antibodies (Sa).…”
mentioning
confidence: 99%